RNA-seq transcriptome characterization of liver, gonad, and head kidney from control and intraperitoneal oil-injected sub-adult male red drum (Gulf of Mexico Research Initiative, 2018)
Illumina high-throughput RNA sequencing technology was used to sequence, assemble and annotate the transcriptome of three tissues; liver, gonad, and head kidney from Sciaenops ocellatus.